2014
DOI: 10.2478/s13374-014-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the effects of an education for peace program: An Israeli perspective

Abstract: Abstract:The aim of the current study was to monitor the changes that individual participants experienced as a result of taking part in a peace education program. The findings of prior analyses led to the understanding that participating in a peace program does not always ensure positive changes and may even cause a regression in attitudes. The present study was conducted in two stages. In the first stage, the researchers learned about the processes that participants underwent during a peace education program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Looking at the Israel–Palestine conflict specifically, there are very few studies that investigated long-term intergroup contact intervention effects quantitatively (e.g., Arnon, 2010; Bar-Natan, Rosen, & Salomon, 2010; Berger, Benatov, Abu-Raiya, & Tadmor, 2016; Jayusi, 2009; Kropiunigg & Pabst, 2007; Schleien, 2007; Schroeder & Risen, 2016; Shani, 2015). Almost all of these studies discovered positive short-term effects, but most of them also revealed that the short-term effects had faded (decreased) at the follow-up measurements.…”
Section: Long-term Contact Intervention Effects In Conflict Areasmentioning
confidence: 99%
“…Looking at the Israel–Palestine conflict specifically, there are very few studies that investigated long-term intergroup contact intervention effects quantitatively (e.g., Arnon, 2010; Bar-Natan, Rosen, & Salomon, 2010; Berger, Benatov, Abu-Raiya, & Tadmor, 2016; Jayusi, 2009; Kropiunigg & Pabst, 2007; Schleien, 2007; Schroeder & Risen, 2016; Shani, 2015). Almost all of these studies discovered positive short-term effects, but most of them also revealed that the short-term effects had faded (decreased) at the follow-up measurements.…”
Section: Long-term Contact Intervention Effects In Conflict Areasmentioning
confidence: 99%